2007
DOI: 10.1677/joe-06-0070
|View full text |Cite
|
Sign up to set email alerts
|

The regulation of stearoyl-CoA desaturase gene expression is tissue specific in chickens

Abstract: Emerging evidence suggests a potential role of stearoyl-CoA desaturase (SCD)-1 in the control of body weight and energy homeostasis. The present study was conducted to investigate the effects of several energy balance-related factors (leptin, cerulenin, food deprivation, genotype, and gender) on SCD gene expression in chickens. In experiment 1, 6-week-old female and male broiler chickens were used. In experiment 2, two groups of 3-week-old broiler chickens were continuously infused with recombinant chicken lep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0
4

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 59 publications
2
25
0
4
Order By: Relevance
“…Moreover, our results also show lower mRNA expression levels in SAT from morbidly obese patients and controls than in VAT. Thus, SCD1 mRNA expression in humans may differ according to the tissue examined, as has been found in animals (18) and with other genes (17), and may suggest a different regulation of SCD1 mRNA expression in VAT and SAT. SCD1 mRNA expression is also highly regulated by fasting/refeeding.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Moreover, our results also show lower mRNA expression levels in SAT from morbidly obese patients and controls than in VAT. Thus, SCD1 mRNA expression in humans may differ according to the tissue examined, as has been found in animals (18) and with other genes (17), and may suggest a different regulation of SCD1 mRNA expression in VAT and SAT. SCD1 mRNA expression is also highly regulated by fasting/refeeding.…”
Section: Discussionmentioning
confidence: 84%
“…Besides, mRNA expression may differ according to the tissue examined (17,18). Different studies have shown the regulation of SCD1 synthesis and activity (14)(15)(16)(17)(18).…”
Section: Stearoyl-coa Desaturase-1 Is Associated With Insulin Resistamentioning
confidence: 99%
“…Mammalian adipocytes produce and secrete more leptin in bloodstream as fat storage increases (Maffei et al,'95) signaling the brain via leptin receptor (Schwartz et al,'96) and modulating hypothalamic feeding-related neuropeptides to suppress appetite and increase energy expenditure (Friedman and Halaas,'98). Surprisingly, leptin specifically inhibits the expression of mammalian lipogenic genes such as fatty acid synthase (FAS, a key enzyme in lipogenesis) (Fukuda et al,'99) and stearoyl-CoA desaturase (SCD, the rate-limiting enzyme in the biosynthesis of monounsaturated fatty acids from saturated fatty acids) (Cohen et al, 2002), but not in chickens (Dridi et al, 2005(Dridi et al, , 2007 suggesting species-related differences in fat metabolism and deposition.…”
mentioning
confidence: 99%
“…Acetylcoline-induced insulin secretion is suppressed by leptin in chicken pancreatic islet cells (Benomar et al, 2003), and insulin reduces LEPR mRNA expression in chicken hepatoma cells (Cassay et al, 2003). Leptin increases mRNA expression of FAS (Dridi et al, 2005) and stearoyl-CoA desaturase (Dridi et al, 2007) in the liver of broilers. Furthermore, in ovo leptin administration upregulates mRNA expression of sterol regulatory element binding protein-1 (SREBP-1c), SREBP-2, hydroxyl-3-methylgulutaryl coenzyme A reductase, and cholesterol 7a hydroxylase 1 at hatching.…”
Section: Food Intake and Metabolismmentioning
confidence: 97%